Human Capital Development in Islamic Education History: Environmental Value and Character Formation in Pesantren - Kodrattulloh Sidiq (PT Keberlanjutan Strategis Indonesia, 2026)
The growing emphasis on sustainable human resource management (HRM) underscores the importance of integrating environmental values into human capital development. However, existing studies predominantly focus on contemporary managerial frameworks, with limited attention to historically rooted and value-based educational systems. This study addresses this gap by examining the role of Islamic educational history in shaping environmentally responsible human capital, with particular reference to pesantren as indigenous Islamic institutions. This research employs a qualitative historical design, utilizing a systematic literature review and thematic content analysis of classical Islamic texts, historical records, and contemporary scholarly works on pesantren. The analytical framework is grounded in Human Capital Theory and Sustainable HRM perspectives. The findings reveal that pesantren have long institutionalized environmental ethics through processes of value internalization, disciplined practices, and communal living, which foster behavioral competencies aligned with sustainability principles. These institutions function as early models of integrated human capital development, incorporating ethical, social, and environmental dimensions. This study contributes to the HRM literature by offering a non-Western, historically grounded perspective on sustainable human capital development. It also provides practical insights for integrating ethical and sustainability-oriented values into contemporary human resource development strategies, particularly in supporting responsible governance practices